PERAN WANITA HINDU DALAM MEMPERSIAPKAN UPAKARA DI LABUAN BAJO MANGGARAI BARAT NUSA TENGGARA TIMUR - Diah Nirmala Dewi; Kadek Tedy Mandala Putra (UHN IGB Sugriwa Denpasar, 2022)
Women, if studied scientifically, the origin of the word Svanittha is found in Sanskrit which has the meaning of the word Sva, which is itself and the word Nittha means holy. The actual meaning of the word Svanittha is to purify oneself, then its meaning is expanded to be about humans who have a big/important role in the Dharma or can be called practitioners of Dharma teachings. In the teachings of Hinduism, women have a very important role, namely as a means to realize the belief in Punarbhawa or the reincarnation of descendants. With the term Punarbhawa also developed the term Sukla Svanittha which means seeds or fetuses conceived by women. Family in Hinduism also has a different meaning. In Sanskrit the word family is divided into two parts, namely Kula and Varga. Kula is interpreted as a servant, servant and Varga is interpreted as a relationship, bond, devotion. Explanation of the meaning of family from Sanskrit, namely the relationship and bond of devotion between husband, wife, and children. Apart from being practitioners of Dharma teachings and successors of descendants, Hindu women are also required to be able to complete their own tasks related to the upkaras used during Yadnya ceremonies.